Hexamilion and Varna - Dąbrowska, Małgorzata (Balcanica Posnaniensia. Acta et studia, 1997)
The article analyzes Byzantium’s attitude toward the events connected with the Battle of Varna and the significance of the Hexamilion fortifications for imperial policy in 1444. The research problem concerns the ambivalent stance of Emperor John VIII Palaiologos toward the Christian–Ottoman conflict and Byzantium’s place in the rivalry between the Turks and the West. This issue is important for understanding late Byzantine policy toward the Turkish threat and the Florentine Union. The aim of the study is to reinterpret Emperor John VIII’s position and to assess the impact of the events at Varna on the situation of the Empire. The author makes use of Byzantine sources, contemporary political correspondence, and modern historiography concerning the Florentine Union and fifteenth-century Balkan policy. The article demonstrates that Byzantium was interested in weakening the Turks, yet at the same time feared the excessive strengthening of the Latin states. The author challenges the authenticity of the letter attributed to John VIII urging King Władysław III to break the peace treaty with the Turks, arguing that such a policy was not in Byzantium’s interest. The most advantageous situation for the Empire was the temporary weakening of both sides of the conflict, which enabled Constantine Palaiologos to rebuild the Hexamilion fortifications and recover influence in the Peloponnese. The results of the analysis indicate that the Battle of Varna was an ambiguous event for Byzantium, while imperial policy remained cautious and defensive in character.